2019
DOI: 10.21474/ijar01/9418
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antimicrobial Activity of Moringa Oleifera and Azadirachta Indica Leaves Against Enterococcus Faecalis, Candida Albicans - An Invitro Study.

Abstract: Objective: To evaluate the antibacterial activity of triple antibiotic paste, Moringa oleifera, Azadirachta indica against Enterococcus faecalis and Candida albicans. Methods: .The extracts of Azadirachta indica and Moringa oleifera were prepared in vitro and the antibacterial effect of the extracts against Enterococcus faecalis and Candida albicans was evaluated using the agar diffusion technique. Results:The study showed that A.indica has a highest inhibitory growth (17.0mm) followed by A.indica and M.oleife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies showed that OCT has a potent antimicrobial effect against E. faecalis [ 16 , 17 ]. In this study, M. oleifera plant was chosen as it has a wide range of antimicrobial properties which have been investigated by some studies, which examined different parts of the plant and different methods of preparation of extract [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed that OCT has a potent antimicrobial effect against E. faecalis [ 16 , 17 ]. In this study, M. oleifera plant was chosen as it has a wide range of antimicrobial properties which have been investigated by some studies, which examined different parts of the plant and different methods of preparation of extract [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted by Shetty et al (2019), Moringa oleifera and Azadirachta indica demonstrated an antibacterial effect against Enterococcus faecalis. They concluded that these natural products could be used effectively as antimicrobial agent in root canal therapy.…”
Section: Discussionmentioning
confidence: 99%